(untitled) (Praxis Educativa, 2016)
Across the globe, the forces of neoliberalism, or what might be called the latest stage of predatory capitalism, are on the march dismantling the historically guaranteed social provisions provided by the welfare state. This is all the more reason for educators and others to address important social issues and to defend public and higher education as democratic public spheres; educators need a new political and pedagogical language for addressing the changing contexts and issues developing forms of critical pedagogy capable of challenging neoliberalism and other anti-democratic traditions. This paper presents the notion of teachers as public intellectuals, pedagogy and the project of insurrectional democracy, pedagogy and the politics of responsibility, and finally, pedagogy as a form of resistance and educated hope. Educated hope provides the basis for dignifying our labor as intellectuals; it offers up critical knowledge linked to democratic social change, it is rooted in shared responsibilities, and allows teachers and students to recognize ambivalence and uncertainty as fundamental dimensions of learning. Such hope offers the possibility of thinking beyond the given—and lays open a pedagogical terrain in which teachers and students can engage in critique, dialogue, and a struggle for social justice.